PERUBAHAN KADAR DEBU UDARA SAAT “CAR FREE DAY” DI SURABAYA TAHUN 2016 - Safitri Praneliani; Khambali .; Marlik . (Poltekkes Kemenkes Surabaya, 2016)
Level of dust particles (PM10) in Surabaya is the highest in East Java because of the increasing number ofmotor vehicles. To reduce exhaust emissions of motor vehicles which produce dust particles (PM), thegovernment of Indonesia has launched the Langit Biru / Blue Sky program with Car Free Day as one of itsprograms. This study aims to determine differences of air dust level at Car Free Day and non-Car Free Day inDarmo street, Surabaya. The design of research is analytic research. The research object was along Darmostreet. The data werecollected by using survey with cross sectional approach and the data were proceeded the form of editing,tabulation and textular. The results of the study shows that the average temperature, humidity, wind speed and the amount ofdust in the air during the Car Free Day were 28.78 oC, 76.22%, 1.48 m/s and 135 mg/Nm respectively and inthe absence of Car Free Day were 28.55 oC, 77.40%, 1.13 m/s and 388.16 mg/Nm respectively.There was significant difference in the dust level (PM103100 3) in the air during the Car Free Day and Non Car Free Day. It is advisable for the government to consider changing the technical implementation of the Car Free Day such as adding more day.Keywords : Dust particles (PM), Car Free Day, Air Pollution